2018
DOI: 10.1016/j.pvr.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 viral characteristics in primary, recurrent and metastatic vulvar carcinoma

Abstract: Vulvar carcinoma is the fourth most common gynecological malignancy. Two separate carcinogenic pathways are suggested, where one is associated with the human papillomavirus (HPV) and HPV16 the most common genotype.The aim of this study was to evaluate HPV-markers in a set of primary tumors, metastases and recurrent lesions of vulvar squamous cell carcinomas (VSCC). Ten HPV16-positive VSCC with metastatic regional lymph nodes, distant lymphoid/hematogenous metastases or local recurrent lesions were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Although VL somewhat varied between time points, the results in individual patients were relatively constant. The authors concluded that time elapsed and new milieu (lymph node or metastasis) seem to have no influence on VL [21]. The patients enrolled in that study were treated with surgery, and therefore the influence of treatment was negligible.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although VL somewhat varied between time points, the results in individual patients were relatively constant. The authors concluded that time elapsed and new milieu (lymph node or metastasis) seem to have no influence on VL [21]. The patients enrolled in that study were treated with surgery, and therefore the influence of treatment was negligible.…”
Section: Discussionmentioning
confidence: 95%
“…We found that HPV16 VL was higher in treatment-naive than in recurrent cancer, but the difference was not statistically significant. As we were not able to find any study comparing HPV16 VL between treatment naive and recurrent anal cancer, we referred to a study on primary and recurrent HPV-dependent vulvar cancer [21]. There were no differences in HPV16 VL between primary vulvar squamous cell cancer and matched local recurrences and/or metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic role of HPV in vulvar SCC is still a matter of debate; however, increasing evidence suggests that HPV-associated tumors are less aggressive (14). A large meta-analysis by Faber et al (16) included > 5000 vulvar cancer patients; the prevalence of HPV was 39.7%. Our HPV-tested patients had a higher percentage of positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of CD36 and LAMA3 protein expression in these samples is warranted to understand whether these proteins are disrupted and whether that may have played a role in metastasis. Our assessment of tumor clonality was limited to HPV genotype and HPV integration site, which other groups have also used to demonstrate tumor clonality [ 43 , 44 ], but future work will include mutational profiling of cellular genes to strengthen our ability to assess the clonal nature of these samples. This work was somewhat limited by having access to only FFPE tissue, resulting in a lack of quality RNA for integrated viral transcript analysis.…”
Section: Discussionmentioning
confidence: 99%